Faktor Kriteria Untuk Menentukan Pondasi Dalam - BAGASKARA, DHEVA PRASETYA (Universitas Negeri Surabaya, 2023)
In daily life, humans always encounter problems about decision making. Decision-making systems can solve problems by providing relevant data information, analytical models, and decision-making tools. The Muhammadiyah Gresik Hospital Construction Project is a multi-storey building construction project that is used as a case study in research conducted on foundation selection. There are several criteria that need to be done in determining foundation selection. The type of research used is applied research by compiling and creating an additional document as a validation of project documents with a decision-making support system obtained through literature studies, discussions and interviews in determining foundation selection. The results showed that there were 10 criteria that emerged from the literature study and there were 13 determination criteria obtained through discussions and interviews in selecting the type of foundation.